Factors that influence job satisfaction among employees in Felda Global Ventures Plantations (M) Sdn.Bhd. / Muhammad Shyrell Junaidi - Junaidi, Muhammad Shyrell (Faculty of Business and Management, 2014)
The aim of this paper is to conduct a research on the relationship between the three factors influence job satisfaction which is pay, promotion, the work itself in Felda Global Ventures Plantations (M) Sdn.Bhd. This company will be assessed and it will be used to determine the factors of employee job satisfaction. The hypotheses that have been made for this study is there are significant relationship between the job satisfactions in Felda Global Ventures Plantations (M) Sdn.Bhd. with the three factors. In this research we only used one type of instrument to obtain the data which is questionnaire. A total number of 113 respondents were randomly selected as the sample of the study.This research contributes four variables which is job satisfaction as dependent variable, reward, organizational culture and job characteristic as the independent variables.The instrument used to study factors that influence job satisfaction is questionnaires which were distributed to 113 respondents in Felda Global Ventures Plantations (M) Sdn Bhd. With this study, organizations able to improve their employees level of satisfaction. Our data was analyzed by the “Statistical Package for Social Science” (SPSS Window) version 20.